Feedback Learning & Assessment: A Mutual Relationship - Abdullah, Rahman (Archives of Business Research, 2020)
Assessment is an important tool, mechanism and approach to ensure accreditation, recognition, quality and standardization in any university’s program and courses. A good assessment that is fair, transparent and consistent should be communicated clearly between students and faculty staff to create a learning environment that is conducive to a university setting.